Nonlinear Decoupling in Process Control - Jens G. Balchen (Modeling, Identification and Control, 1991)
The principle of nonlinear decoupling as a general approach to the control of nonlinear processes is reviewed. A novel technique is introduced for resolving the inverse problem in case the nonlinear process function does not have a closed-form inverse. The paper also indicates the relationships between nonlinear decoupling, 'cascade control' and 'sliding mode control'.